Peningkatan Pengetahuan Ibu Hamil tentang Gizi Seimbang di Wilayah Puskesmas Simpang Raya - Widyawati Astuti; Zamli Zamli (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The nutritional awareness of pregnant women in the Simpang Raya Community Health Center (Puskesmas) in Banggai Regency is still relatively low, necessitating educational efforts to increase their understanding of the importance of balanced nutrition during pregnancy. This community service activity aims to improve the knowledge of pregnant women through participatory and educational nutrition counseling held for one week in the Puskesmas hall. The methods used included interactive lectures, group discussions, and healthy menu preparation simulations, supported by leaflets adapted to the local context. A total of 40 pregnant women from various trimesters of pregnancy participated in the activity and were assessed using pre- and post-test instruments. The results of the activity showed a significant increase in participant knowledge, from 43% in the "good" category before the activity to 78% after the counseling. Most participants were able to understand the basic principles of balanced nutrition, identify food sources of important nutrients such as iron and folic acid, and prepare daily menus according to Ministry of Health guidelines. This improvement indicates that visual and interactive information delivery is easier for participants to understand, especially those with lower educational backgrounds. Furthermore, this activity also serves as a means of empowering pregnant women to be more active in maintaining their own and their fetus' health by choosing nutritious foods. Therefore, it is crucial for health workers at community health centers (Puskesmas) and integrated health post (Posyandu) cadres to continue this educational program on an ongoing basis. Structured, communicative, and participatory nutrition education is effective in increasing pregnant women's understanding and can be replicated periodically at other Posyandus (Integrated Health Posts) to support stunting prevention efforts and improve maternal and child health.